PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. PILAR LANGGENG SEJAHTERA - Dwi Prihantono (Fakultas Ekonomi Universitas 45 Surabaya, 2015)
This study aims to determine simultaneously the influence of corporate culture on employee performance and motivation, knowing the partial effect of corporate culture and motivation on employee performance and determine the dominant variable affecting the performance of employees of PT. Pilar Langgeng Sejahtera. This study uses a quantitative approach, the research is more emphasis on the objective measurement of the social phenomenon with a shot in the PT. Pilar Langgeng Sejahtera. Malang and the sample is determined by sampling a total of 61 employees. Variables in this research is Corporate Culture, Employee Motivation and Performance. The data analysis technique used is to use Regression Analysis, F test and t test. Based on the calculation t test that has been done can be seen that the independent variables partially significant effect on the dependent variable. It is known from tcount independent variables that have a greater value than ttable. Regression coefficient of each independent variable is X1: 0.986; X2: 0.181 -1.749 constant. Corporate culture variables (X1) is a variable that dominant influence on employee performance with a beta value of 0.986. Meanwhile, the value of R2 is 0.927, which means that the independent variables affect significantly by 92.7% to the dependent variable, while the remaining 7.3% is influenced by other variables outside the research variables.